2011
DOI: 10.1038/bmt.2011.156
|View full text |Cite
|
Sign up to set email alerts
|

Oral cryotherapy can significantly reduce oral mucositis but not acute GVHD incidence in Flu/Mel conditioning allo-SCT

Abstract: influenced the detailed results of our analysis: more peripheral SC grafts and lower MTX dose administered in the non-cryotherapy group, fewer sibling donor transplantations in cryotherapy group, some patients lost from observation for mortality reasons before day þ 100 without developing acute GVHD. We assume, however, that our findings are potent enough to state, that even although oral cryotherapy significantly reduced OM, it had no impact on acute GVHD incidence reduction. Our findings do not exclude OM fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…However, Vokurka et al, [68] found no evidence for this notion in a study in which OM was prevented by oral cryotherapy in allogeneic HSCT recipients treated with high-dose melphalan conditioning regimens [68]. …”
Section: Oral Mucositismentioning
confidence: 99%
“…However, Vokurka et al, [68] found no evidence for this notion in a study in which OM was prevented by oral cryotherapy in allogeneic HSCT recipients treated with high-dose melphalan conditioning regimens [68]. …”
Section: Oral Mucositismentioning
confidence: 99%
“…There have been no more than 150 patients reported in the literature who underwent cryotherapy during melphalan infusion. In general, the prospective studies demonstrated a good response to minimizing OM severity during HSCT .…”
Section: Discussionmentioning
confidence: 85%
“…The principle of cryotherapy has not been fully elucidated. It has been postulated that reduction in the local temperature leads to vasoconstriction in the oral mucosa and decreases the exposure to melphalan . This temperature‐dependent reduction in the cytotoxicity of melphalan also induces impairment in the production of chemical mediators that are related to the pathogenesis of OM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In standard radiotherapy protocols, however, this intervention is ineffective (19)(20)(21). Oral cryotherapy can significantly reduce oral mucositis in Fluorouracil/Melphalan conditioning allogenic Stem Cell Transplantation (22,23).…”
Section: Cryotherapy (Ice Chips)mentioning
confidence: 98%